Genotypic and phenotypic analysis of backcross inbred lines for brown plant hopper resistance in rice - Garima Pelhania1 , M. Gokulakrishnan1 , J. Niranjana Devi1 , S. Yazhini1 , V. Balasubramani1 , S. Manonmani2 , Sheela Venugopal2 and J. Ramalingam1* (Electronic Journal of Plant Breeding, 2023)
The most devastating insect pest of rice, Brown plant hopper (BPH) (Nilaparvata lugens Stal.) feeds on the rice plant and results in huge yield loss. Breeding of resistant cultivars is more economical and eco-friendlier than use of chemical pesticides. Rice cultivars with improved resistance to disease and pest are developed with pyramiding techniques to incorporate the stronger resistance genes in single plant. In this study, CO51, a popular elite variety of Tamil Nadu, improved with introgression of bacterial blight and blast resistance genes was used as a recurrent parent and BPH resistance genes were introgressed in it using marker-assisted selection (MAS) method of breeding. The lines having multiple resistance genes were evaluated using foreground and agronomic trait selection and forwarded toBC2 F4 generation. The bioassay of selected twenty-seven lines showed either single or both gene introgression enhanced resistance than the recurrent parent.